2014
DOI: 10.1002/term.1914
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myogenic differentiation of human urine-derived cells as a potential source for skeletal muscle regeneration

Abstract: Stem cells are regarded as possible cell therapy candidates for skeletal muscle regeneration. However, invasive harvesting of those cells can cause potential harvest-site morbidity. The goal of this study was to assess whether human urine-derived stem cells (USCs), obtained through non-invasive procedures, can differentiate into skeletal muscle linage cells (Sk-MCs) and potentially be used for skeletal muscle regeneration. In this study, USCs were harvested from six healthy individuals aged 25-55. Expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Therefore, adult stem cells, such as MSCs are a suitable source of cells for stem cell therapy, and may be used to promote the regeneration of damaged SKM. In a number of studies, stem cells derived from bone marrow, adipose tissue, the placenta, amniotic fluid, umbilical cord blood and urine have shown potential to promote SKM regeneration ( 1 , 11 14 , 18 ). However, the degree of regeneration obtained when using these cells may be insufficient when the injury or damage is severe ( 1 , 11 14 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, adult stem cells, such as MSCs are a suitable source of cells for stem cell therapy, and may be used to promote the regeneration of damaged SKM. In a number of studies, stem cells derived from bone marrow, adipose tissue, the placenta, amniotic fluid, umbilical cord blood and urine have shown potential to promote SKM regeneration ( 1 , 11 14 , 18 ). However, the degree of regeneration obtained when using these cells may be insufficient when the injury or damage is severe ( 1 , 11 14 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have been performed using stem cells in order to treat muscle-related diseases in which the organization of muscle tissue is adversely affected by congenital hereditary muscle defects, loss of muscle mass, trauma or tumor removal ( 1 5 ). Previous studies have reported the transplantation of muscle stem cell-derived myoblasts or myogenic cells in models of muscle injury ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogels are also excellent carriers for drug loading and allow long time and spatio-temporal drug releases [158,159]. In one study, Liu et al differentiated human urine-derived stem cells (USCs) into a myogenic lineage by culturing them on alginate microbeads encapsulating a cocktail of growth factors and then subcutaneously engrafted these cells into nude mice [97,160]. Hydrogels can also be designed to be injectable.…”
Section: Nanofiber Scaffoldsmentioning
confidence: 99%